Syariah Government Credit Card: Reframing Public Expenditure Management Through Islamic Financial Principles in Indonesia - Kian, Lia; Abas, Sofyan; Mansir, Firman (Al-Amwal : Jurnal Ekonomi dan Perbankan Syari'ah, 2026)
Introduction: This study aims to redefine public expenditure management in Indonesia through the lens of Islamic finance principles. It seeks to provide insight into the outcomes associated with the concept of an Sharia government credit card (SGCC), highlighting its significance in optimizing state expenditure management. Additionally, the research endeavors to develop an evaluation framework for SGCCs grounded in key Islamic precepts: ḥifẓ al-dīn (adherence to Islamic values), ḥifẓ al-māl (safeguarding state resources), maslaha ammah (ensuring public welfare), ḥifẓ al-nafs (effective risk mitigation), and ḥifẓ al-'aql (rational oversight and accountability) within the context of public finance and government payment system reforms.Methods: This study adopts a descriptive and qualitative approach, utilizing document analysis of public finance policy documents, SGCC, and sharia principles. Data collection from the literature was carried out through a Systematic Literature Review (SLR) method, involving a structured search across Scopus, Web of Science (WoS), and Google Scholar.Results: Revisiting public expenditure management in Indonesia through the lens of Islamic financial principles aligns with the growing need for a more integrated state financial management policy within the national budget and revenue framework. This approach is guided by public financial policy commitments established in laws and regulations issued by relevant Ministries and Institutions. From the standpoint of public finance, and specifically through a sharia perspective, the normative and regulatory frameworks provide integrative reasoning that directly supports the concept of Sharia Government Credit Cards (SGCC).Conclusion and suggestion: Empirical evidence regarding the governance and effectiveness of state expenditure highlights the merits of initiatives like Government Credit Cards, offering valuable insights that can be adapted to strengthen the SGCC framework.